Oral mucosa hyperpigmentation as a presentation of Laugier-Hunziker syndrome: a case report (Portuguese Journal of Family Medicine and General Practice, 2022)
Introduction: Pigmented lesions of the oral cavity can be caused by local changes or configure manifestation of systemic disease. It is important to recognize the main etiologies of these lesions in order to identify, timely, the need for intervention and treatment.Case description: We report a case of an 89-year-old woman who, in a diabetes surveillance consultation, complained of the pigmented tongue, with months of evolution, without pain or other associated symptoms. The patient was referred to the dermatologist, where a biopsy of one of the lesions was performed, which revealed a melanotic macula of the oral mucosa. Considering clinical features and histological findings, the diagnosis of Laugier-Hunziker syndrome (LHS) was done. The patient was informed of the benignity of the condition and the absence of the need for treatment.Comment: LHS is a benign mucocutaneous disease, of acquired character, characterized by multiple hyperpigmented macules, most often present in the oral mucosa or lips. Although rare, it is a benign and acquired disease and constitutes a diagnosis of exclusion. The article intends to report a rare syndrome with dermatological manifestations and to address the differential diagnosis of hyperpigmented lesions of the oral mucosa.
Keywords: Laugier-Hunziker syndrome; Hyperpigmentation; Mouth mucosa, Abnormalities; Case report